Environmental soil contamination with zoonotic soil-transmitted helminths in the temple grounds of Chachoengsao Province, Thailand - Amornrat Dokmaikaw; Pisit Suntaravitun (International Journal of One Health, 2023)
Background and Aim: Soil-transmitted helminth infections are a serious public health problem. The soil is an important reservoir for several helminth species. This study aimed to estimate the prevalence of soil contamination with zoonotic soil-transmitted helminths.